An Unreported Complication After Fetoscopic Myelomeningocele Closure. Issue 2 (March 2019) - Ewing, Donald C.; Dempsey, Robert; Belfort, Michael A.; Olutoye, Oluyinka O.; Whitehead, William E.; Hollier, Larry H.; Buchanan, Edward P.
Abstract : Abstract: Myelomeningocele (MMC) is a type of open neural tube defect characterized by exposure of the spinal cord through a defect in the skin and posterior hindbrain herniation through the foramen magnum. Outcomes vary but common morbidities include paraplegia, hydrocephalus, neurogenic bladder, scoliosis, and tethered cord. Fetal surgery, although not a cure, has been shown to decrease the risk of associated morbidity. A study of a neonate born at 39 5/7 weeks gestation status-post in utero fetoscopic MMC repair at 24 weeks gestation was presented in this study along with a concise review of the literature. Fasciocutaneous advancement flaps were made in utero to facilitate a tension-free midline closure and were left to heal secondarily. The neonate underwent uncomplicated spontaneous vaginal delivery but was noted to have a right flank hernia through the relaxing incision in addition to delayed healing of the left relaxing incision. According to authors, iatrogenic flank hernia following fetoscopic MMC repair has not been previously reported in the literature. Both defects were repaired primarily in layers with undermining and retroperitoneal domain was reestablished with imbrication of the overlying muscle on the right side. The authors report their experience to contribute to the scarce literature describing postnatal complications arising from this novel procedure.